Nanobody-based chimeric antigen receptor T cells designed by CRISPR/Cas9 technology for solid tumor immunotherapy - Fengzhen Mo; Siliang Duan; Xiaobing Jiang; Xiaomei Yang; Xiaoqiong Hou; Wei Shi; Cueva Jumbo Juan Carlos; Aiqun Liu; Shihua Yin; Wu Wang; Hua Yao; Zihang Yu; et al. (Signal Transduction and Targeted Therapy, 2021)
Abstract Chimeric antigen receptor-based T-cell immunotherapy is a promising strategy for treatment of hematological malignant tumors; however, its efficacy towards solid cancer remains challenging. We therefore focused on developing nanobody-based CAR-T cells that treat the solid tumor. CD105 expression is upregulated on neoangiogenic endothelial and cancer cells. CD105 has been developed as a drug target. Here we show the generation of a CD105-specific nanobody, an anti-human CD105 CAR-T cells, by inserting the sequences for anti-CD105 nanobody-linked standard cassette genes into AAVS1 site using CRISPR/Cas9 technology. Co-culture with CD105+ target cells led to the activation of anti-CD105 CAR-T cells that displayed the typically activated cytotoxic T-cell characters, ability to proliferate, the production of pro-inflammatory cytokines, and the specific killing efficacy against CD105+ target cells in vitro. The in vivo treatment with anti-CD105 CAR-T cells significantly inhibited the growth of implanted CD105+ tumors, reduced tumor weight, and prolonged the survival time of tumor-bearing NOD/SCID mice. Nanobody-based CAR-T cells can therefore function as an antitumor agent in human tumor xenograft models. Our findings determined that the strategy of nanobody-based CAR-T cells engineered by CRISPR/Cas9 system has a certain potential to treat solid tumor through targeting CD105 antigen.